Efeito da suplementação de cromo em dois níveis energéticos para poedeiras leves - Siloto, Estela Valéria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
O presente estudo avaliou o efeito da suplementação do cromo e dois níveis de energia sobre o desempenho e a qualidade de ovos de poedeiras leves. Foram utilizadas 192 poedeiras da linhagem Bovans com 47 semanas de idade. As aves foram distribuídas em um delineamento inteiramente casualizado, em esquema fatorial 4x2, com quatro níveis de suplementação de cromo (0, 200, 400 e 800 μg Cr/kg) e dois níveis energéticos (2.780 e 2.900 kcal EM/kg de ração). Cada tratamento continha seis repetições de quatro aves cada. O cromo utilizado foi o derivado de levedura. O experimento teve a duração de 112 dias, divididos em 4 períodos de 28 dias. Os parâmetros de desempenho não foram influenciados pelos níveis de cromo e de energia da dieta. Houve aumento linear no percentual de gema com o aumento da suplementação de cromo em dietas contendo 2.780 kcal/kg. As aves alimentadas com dietas contendo 2.780 kcal de EM/kg e isentas de suplementação de cromo, apresentaram redução no percentual de gema. Quando as aves foram suplementadas com 800 μg Cr/kg de dieta, foi observada uma maior deposição de gema. A suplementação de 800 μg Cr/kg na dieta com 2.780 kcal EM/kg provocou aumento no percentual de gema sem afetar o desempenho das poedeiras

This study aimed to evaluate the performance and egg quality in laying hens receiving diets supplemented with crescent levels of Chromium yeast and two different dietary energy levels. One hundred and ninety-two 47-week-old Bovans laying hens were distributed in a completely randomized design with 4x2 factorial arrangement: 4 levels of chromium yeast supplementation (0, 200, 400, 800 μg/kg feed) and two energy levels (2,780 and 2,900 kcal ME / kg of feed). Each treatment consisted of 6 replications of 4 birds each. The experiment lasted 112 days (four 28-day periods). The following performance parameters were evaluated: feed intake, egg weight, egg production, percentage of whole eggs, egg mass, feed: gain ratio (kg feed/dozen eggs and kg feed/kg eggs). The egg quality was accessed through the weight of total egg, shell, yolk and albumen and their proportions, Haugh unit, the specific gravity, and the shell thickness. The performance parameters were not influenced by the levels of chromium and dietary energy. There was a linear increase in the percentage of yolk with increasing chromium supplementation in diets containing 2.780kcal/kg. Laying hens fed with diets containing 2.780kcal/kg ME and without chromium supplementation showed reduced percentage of yolk. When birds were supplemented with 800 mg Cr / kg diet a greater deposition of yolk was observed. Dietary supplementation of 800 mg Cr / kg with 2.780kcal of ME/kg induced an increase in the percentage of yolk without affecting performance of laying hens
Keywords: Ave poedeira - Nutrição; Lipidios - Metabolismo; Cromo na nutrição animal; Ovos - Produção; Energia; Lipid - Metabolism -Disorders